Consumtivism on Touring Master’s Students In Jakarta - Linda Kusumaning Wedari (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2016)
This study about the factors that influence the decision on tourism destination of Master’s students from 9 (nine) Universities in Jakarta. Around 199 questionnaires that were returned, had been processed by using binary logistic regression, for tour in Java, tour outside of Java, domestic tourism, and tour overseas. The researcher finds that, First, respondents make expenditures for meals, snacks, entrance fees, game with consumptive. While spending on hotels, their clothes, clothes for gift, souvenirs and snacks for gift with highly consumptive. Second, factors that encourage a trip decision to Java and outside Java, are income and plan (respondents prepared it by their monthly saving) while factors that influence them to have trip in the country (domestic)or overseas, are motivation, spending, and income. Third, for both trip to Java Island and outside Java Island, and also tourism domestic destinations as well as overseas, most respondents choose to pay their cost by their own cash or by their own credit card for the range of 1-6 months payment.